2016
DOI: 10.1002/2016jd025533
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet analysis of precipitation extremes over Canadian ecoregions and teleconnections to large‐scale climate anomalies

Abstract: To detect significant interannual and interdecadal oscillations and their teleconnections to large‐scale climate anomalies such as El Niño–Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), and North Atlantic Oscillation (NAO), monthly and seasonal maximum daily precipitation (MMDP and SMDP) from 131 stations across Canada were analyzed by using variants of wavelet analysis. Interannual (1–8 years) oscillations were found to be more significant than interdecadal (8–30 years) oscillations for all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 60 publications
0
37
0
1
Order By: Relevance
“…Wavelet transform has been widely used in different research works worldwide to analyze time series of ENSO [79], to identify and describe the variability in annual streamflows [4], and interannual, decadal, and multidecadal climate oscillations of annual discharge [80]. This method was also used to understand mechanisms driving streamflow variability at all timescales [81], and to analyze precipitation extremes and their teleconnections with large-scale climate anomalies [82], among others.…”
Section: Wavelet Transformmentioning
confidence: 99%
“…Wavelet transform has been widely used in different research works worldwide to analyze time series of ENSO [79], to identify and describe the variability in annual streamflows [4], and interannual, decadal, and multidecadal climate oscillations of annual discharge [80]. This method was also used to understand mechanisms driving streamflow variability at all timescales [81], and to analyze precipitation extremes and their teleconnections with large-scale climate anomalies [82], among others.…”
Section: Wavelet Transformmentioning
confidence: 99%
“…Wavelet analysis was widely applied to examine multi-temporal scale features of precipitation extremes or other climate events [59][60][61][62][63][64][65]. Wavelet transform (WT) decomposes time series into time-frequency space and identifies the dominant modes of variability and the characteristics how these modes vary in time [66]. Continuous wavelet transform (CWT) is appropriate for extracting a wide range of possible dominant frequencies from geophysical and hydroclimate time series [67,68].…”
Section: Wavelet Analysismentioning
confidence: 99%
“…The study further reported that the influence of ENSO on precipitation was stronger compared to other climatic modes considered in this particular study. Coherently, Tan et al (2016) analysed the relations between Canadian precipitation and different global climate indices. Similar studies using wavelet coherence also reported in other parts of the world (Agarwal et al, 2016;Araghi et al, 2017;Hu and Si, 2016;Tan et al, 2016), though all such studies based on wavelet coherence were illuminating and contributed significantly to our existing knowledge of the climate.…”
Section: Introductionmentioning
confidence: 99%
“…Coherently, Tan et al (2016) analysed the relations between Canadian precipitation and different global climate indices. Similar studies using wavelet coherence also reported in other parts of the world (Agarwal et al, 2016;Araghi et al, 2017;Hu and Si, 2016;Tan et al, 2016), though all such studies based on wavelet coherence were illuminating and contributed significantly to our existing knowledge of the climate. However, there remains a large scope for advancement, in particular in capturing the non-linear scalespecific interactions between climate patterns and Indian precipitation.…”
Section: Introductionmentioning
confidence: 99%